Role of Mahatma Gandhi In Freedom Struggle of India: The Contribution of Mahatma Gandhi to India's Freedom Struggle (Journal of Advances and Scholarly Researches in Allied Education, 2015)
One of the greatest men in the history of India is unarguably MahatmaGandhi. The way he gave shape and character to India's freedom struggle isworthy of a standing ovation. He sacrificed his own life for the sake of hiscountry. The respect that he earned for himself despite leading a simplelifestyle is much appreciable. Mahatma Gandhi played a pivotal role in thefreedom struggle of India. His nonviolent ways and peaceful methods were thefoundation for gaining independence from the British.